PENGARUH EFIKASI DIRI TERHADAP HASIL BELAJAR SISWA SEKOLAH DASAR - Nasrah Nasrah; Novianti Novianti; Kaharuddin Kaharuddin (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to determine how the influence self-efficacy on students’ learning outcomes. This research included causal ex-post facto research. The research subjects were elementary school students (SD) with a sample of 27 students. Research data collection was carried out by providing instruments in the form of self-efficacy questionnaires and multiple-choice tests that were used to collect information on science learning outcomes, made by adjusting the basic competencies used in the cognitive domain. The results of this study were based on the calculation of the correlation between self-efficacy and learning outcomes showing a correlation coefficient of 0.029 with p <0.05, meaning Ho was rejected and Ha is accepted, if self-efficacy is good, student learning outcomes will be high. There is a positive and significant correlation between self-efficacy and student learning outcomes. From the results of this study, one of the successes of student learning was seen from the level of self-efficacy so that this assessment can be used as a basis for consideration and solutions for teachers in carrying out the teaching and learning process.